Effectiveness of double-balloon enteroscopy-assisted endoscopic retrograde cholangiopancreatography (DBE-ERCP): A multicenter real-world study. Issue 3 (March 2023) - Farina, Elisa; Cantù, Paolo; Cavallaro, Flaminia; Iori, Veronica; Rosa-Rizzotto, Erik; Cavina, Maurizio; Tontini, Gian Eugenio; Nandi, Nicoletta; Scaramella, Lucia; Sassatelli, Romano; Penagini, Roberto; Vecchi, Maurizio; et al.
Abstract: Background and aims: To investigate the effectiveness of double-balloon enteroscope-assisted retrograde cholangiopancreatography (DBE-ERCP) in patients with gastrointestinal surgically altered anatomy (SAA). Methods: From May 2013 to October 2021, all consecutive patients undergoing DBE-ERCP in three gastroenterological referral centers in Northern Italy were enrolled in the study. Patients were assessed regarding their medical history, previous surgery, time from previous surgery to the DBE-ERCP procedure, and the success or failure of DBE-ERCP. Results: Fifty-three patients (60% men, median age 65 (23–89) years) undergoing 67 DBE-ERCP procedures (1–3 DBE-ERCP per patient) were enrolled. Reasons for SAA included orthotopic liver transplantation (23%), ulcers (15%), malignancies (43%), difficult cholecystectomy (17%), and other causes (2%). Types of surgery included Roux-en-Y biliodigestive anastomosis (45%), Roux-en-Y gastrectomy (32%), pancreaticoduodenectomy (17%), and Billroth II gastrectomy (6%). The overall DBE-ERCP success rate was 86%. The type of surgery, indications, and the length of time between previous surgery and DBE-ERCP were not statistically associated with DBE-ERCP success. The DBE-ERCP success rate increased from 2018 to 2021. Conclusions: DBE-ERCP is a successful procedure in challenging patients with SAA. The improvement in results over time indicates the necessity of adequate training and of centralizing patients in referral centers.